Phylogeny of selected flycatchers (Family : muscicapidae) inferred from mtDNA cytochrome oxidase I gene - Puvaneswari, A/P Puvanasundram (Universiti Malaysia Sarawak, UNIMAS, 2012)
The phylogeny of selected flycatchers (Family: Muscicapidae) was inferred from mtDNA cytochrome oxidase I gene through DNA sequencing analysis. Polymerase chain reaction (PCR) method was incorporated in this study which resulted in approximately 498 base pairs (bp) of end product. Phylogenetic tree was constructed by using Neighbor Joining (NJ), Maximum parsimony (MP), Maximum Likelihood (ML) and Bayesian analysis method. Both NJ and MP produced 2 major clades which separated subfamily Muscicapinae from Monarchinae and Rhipidurinae which is debated to have diverged into a new family. ML and Bayesian analysis proved that genus Rhipidura and Terpsiphone are more closely related to each other than to subfamily Muscicapinae. The study indicates that using cytochrome oxidase I gene can resolve the relationship among species well.